2021
DOI: 10.4103/aja.aja_31_21
|View full text |Cite
|
Sign up to set email alerts
|

Semen parameters in men recovered from COVID-19

Abstract: The novel coronavirus disease (COVID-19) pandemic is emerging as a global health threat and shows a higher risk for men than women. Thus far, the studies on andrological consequences of COVID-19 are limited. To ascertain the consequences of COVID-19 on sperm parameters after recovery, we recruited 41 reproductive-aged male patients who had recovered from COVID-19, and analyzed their semen parameters and serum sex hormones at a median time of 56 days after hospital discharge. For longitudinal analysis, a second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(111 citation statements)
references
References 30 publications
6
80
0
Order By: Relevance
“…Characteristics of the 7 studies are described in Table 1. There were 5 12 13 21 22 , 1 10 , and 1 11 cross-sectional, case-control, and cohort studies, respectively. The participants either recovered from COVID-19 or were without a history of COVID-19 infection -and had a mean age and BMI of 37.34 ± 10.5 and 25.6 ± 0.65, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristics of the 7 studies are described in Table 1. There were 5 12 13 21 22 , 1 10 , and 1 11 cross-sectional, case-control, and cohort studies, respectively. The participants either recovered from COVID-19 or were without a history of COVID-19 infection -and had a mean age and BMI of 37.34 ± 10.5 and 25.6 ± 0.65, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…These changes re ect the unfavorable effect of COVID-19 on the male reproductive system. A longitudinal study carried out among those recovered from COVID-19 observed a negative impact on sperm quality, although these were likely to be reversible 10 . However, Holtman et al found out that adverse effects on sperm count and sperm motility were only detected in hospitalized patients but not in subjects who have recovered after mild symptoms 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, analyses of changes in semen parameters among serial semen samples showed improvements with increasing length of recovery from COVID-19. 15 , 48 These results suggest that the effect of COVID-19 on semen parameters is linked to disease severity; these changes appear to be reversible after recovery from COVID-19.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies concerning specific semen quality parameters have yielded conflicting results. Some studies showed decreases in sperm count, 15 , 46 49 percentage of total motility, 48 50 and percentage of cells with normal morphology 46 in semen samples from patients who had recovered from COVID-19. Other studies have shown no changes in the percentages of total motility 46 or cells with normal morphology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation